Ag nanoparticle decorated graphene for improving tribological properties of fabric/phenolic composites. (December 2022) - Xu, Mingkun; Wang, Xiaoyue; Wang, Tingmei; Wang, Qihua; Li, Song
Abstract: In the present study, graphene nanosheets (GNS) supporting monodispersed Ag nanoparticles (GNS/Ag) hybrid was constructed via an in-situ synthesis. The enhancement mechanism of friction and wear performance of Kevlar/PTFE (Poly-p-phenylene terephthamide)/(Polytetrafluoroethylene) phenolic composites reinforced by GNS/Ag hybrid was investigated by virtue of macroscopic experiments and microscopic molecular (MD) simulation. The results found that Ag nanoparticles were homogeneously anchored on the GNS surfaces. When 9 wt% GNS/Ag hybrid was incorporated into fabric composites, the friction coefficient and wear rate of Fabric-9GNS/Ag decreased by 40 % and 72 % because of synergistic enhancement of GNS and Ag nanoparticles. The MD simulation demonstrated that GNS/Ag hybrid had a strong interaction with molecular chains of PTFE, Kevlar and phenolic resin.